Black Hole Detection Using Modified Sequence Number in Vehicular Ad-hoc Network - Rakha Fikran Julda; Dany Primanita Kartikasari; Rakhmadhany Primananda (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
Vehicular Ad-hoc Network (VANET) is a type of wireless network with Dedicated Short-Range Communication (DSRC) that enables communication between vehicles (V2V) and communication between vehicles to infrastructure around them (V2I). VANET has several security requirements to consider in order to maintain the network functionality. Availability is the most important security requirement due to its responsibility of maintaining the functionality of the network, attack on availability may cause the lack of availability and reduce the efficiency of VANET. One of the attack that threat the availability of VANET is black hole. In this paper, we address the problem of black hole attack in VANET, using Modified Sequence Number (MSN) as a detection method. The simulation is performed using NS-2 as a simulator and AODV as a routing protocol. Detection Rate (DR) and False Alarm Rate (FAR) are used to evaluate the performance of MSN algorithm in detecting black hole attack. Evaluation with variation in the number of CBR packets shows that MSN algorithm successfully detects black hole attacks with DR values reaching 69.0909% at 10 CBR packets and FAR values reaching 0.0037 at 20 CBR packets. We also evaluate the performance of MSN algorithm with variations of node density. The evaluation shows that MSN algorithm successfully detects black hole attack with DR values reaching 100% with a density of 10 and 20 nodes, with the percentage of FAR values reaching 0% in all numbers of node density.